2014
DOI: 10.1007/s10620-014-3381-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation and Endotoxemia After Pringle Maneuver in Cirrhotic Rats

Abstract: There is endotoxemia immediately after Pringle maneuver and gut bacteria translocation 24 h later. The incidence of gut bacterial translocation increases with the duration extension of Pm. Selective intestinal decontamination can decrease bacteria translocation and endotoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…PM, which is commonly used for intraoperative bleeding control in liver surgeries, has been shown to lead BT in mesenteric lymph nodes and portal blood specimens in various experimental and clinical studies [1821]. Our study also showed that PM causes bacterial growth in portal blood and mesenteric tissue cultures in rats.…”
Section: Discussionsupporting
confidence: 68%
“…PM, which is commonly used for intraoperative bleeding control in liver surgeries, has been shown to lead BT in mesenteric lymph nodes and portal blood specimens in various experimental and clinical studies [1821]. Our study also showed that PM causes bacterial growth in portal blood and mesenteric tissue cultures in rats.…”
Section: Discussionsupporting
confidence: 68%
“…A midline laparotomy was performed in 6-IG, 12-IG, 24-IG groups. The PT was ligated according to the standard technique (19) for 6, 12 and 24 minutes, depending on the group of laboratory animals. Successfully performed PT clamping was determined and assessed by the detection of congestion in the intra-abdominal organs.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Preclinical studies indicated a high risk of damage to the small intestine during clamping of the PT. It has been associated with hypo-perfusion of extra-hepatic structures that lead to the manifestation of bacterial translocation and endo-toxinemia (17)(18)(19). However, the different modes of PT clamping cannot provide a clear picture for establishing the optimal time interval to prevent irreversible changes in the structure of the small intestine.…”
Section: Introductionmentioning
confidence: 99%